A Role of Physical Activity in Patients with Systemic Sclerosis – a literature review - Staniszewska, Izabela (Journal of Education, Health and Sport, 2024)
Introduction: Systemic sclerosis (SSc) is a chronic multisystem disease. The condition is characterized by extensive vascular dysfunction and progressive fibrosis of the skin and internal organs. The musculoskeletal, cardiac, pulmonary, and gastrointestinal systems are involved, resulting in a broad range of symptoms. Diagnosis is based on skin and/or internal organ fibrosis, production of specific autoantibodies, and evidence of vasculopathy Purpose of work: Synthesis of knowledge about physical activity in patients with SSc. Summary: Exercise and physiotherapy can improve the physical functions of patients with SSc. Physical activity in patients with SSc enhances hand function, enhances the function of the orofacial region, enhances sexual function, and also aids in coping with Raynaund’s phenomenon, enhances physical capacity, alleviates fatigue as well and enhances general physical capacity. Furthermore, regular physical activity impeded the natural progression of progressive impairment of functional ability. Although, the literature regarding the efficacy and safety of exercise in patients with SSc is further insufficient.